FAKTOR YANG MEMPENGARUHI MOTIVASI WISATAWAN KE DESA WISATA LIANG NDARA KABUPATEN MANGGARAI BARAT - Walbat, Viktorianus; Agus Wikanatha Sagita, Putu; Wijaya, N.M.S. (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
This research was conducted to analysis the factors that influence the motivation of tourists, and to find out the dominant factors that influence the motivation of tourists visiting the Liang Ndara Tourism village of Manggarai Barat Regency. Determination of the sample for tourists using the Accidental sampling method, the analysis technique used in this study is a descriptive quantitative analysis technique with validity, reliability and factor analysis supported by SPSS version 21.0.The result examined of factor analysis, there are three factors that influence the motivation of tourists to visit Liang Ndara Tourism Village, (1) Quality of Facilities Factors consisting of six indicators, namely the availability of public facilities such as toilets and parking area, escape from urban routine, hand-woven crafts and traditional woven textiles made by local, the uniqueness of cultural attractions such as the Caci dance or traditional dance by Manggarai Barat people, the security, natural resources such as waterfall and protected forest, (2) The second factor is Rest and Relaxation factor, which consists of six indicators, namely the desire for physical and mental refreshment, the desire to interact socially with the local community, breaking away from routine work, Liang Ndara Tourism Village location easy to access by vehicle, restaurants facility, Availability of Lodging / accommodation. (3) The third factor is Realize Dreams factor, which consists of two indicators, namely fulfillment of travel dreams, and the desire to visit friends or relatives. The dominant factor of the three factors above is Quality of Facilities.